2014
DOI: 10.3109/01612840.2014.901448
|View full text |Cite
|
Sign up to set email alerts
|

Motivation Does not Come with an Ending—It's the Beginning of Something New: Experiences of Motivating Persons with Psychiatric Disabilities to Physical Activity

Abstract: Despite strong evidence for the positive relationship between physical activity and mental health, physical activity is used far too little to promote health in mental health care. Fourteen caregivers working in community mental health services were interviewed about their experiences of motivating adult persons with psychiatric disabilities to be physically active, and data were analysed using a phenomenological-hermeneutical approach. Three themes emerged: (1) An approach of conscious acts, (2) Companionship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 95 publications
(97 reference statements)
1
2
0
Order By: Relevance
“…Consistent with previous research, this could be provided by mental health professionals such as physiotherapists and occupational therapists [47]. While some people with SMI are comfortable in accepting support from professionals, others do not want this [48] and prefer support from trusted caregivers, friends, and family [49].…”
Section: Thoughts About the Cost And Locationsupporting
confidence: 52%
“…Consistent with previous research, this could be provided by mental health professionals such as physiotherapists and occupational therapists [47]. While some people with SMI are comfortable in accepting support from professionals, others do not want this [48] and prefer support from trusted caregivers, friends, and family [49].…”
Section: Thoughts About the Cost And Locationsupporting
confidence: 52%
“…It has been shown that social support is required to help an individual with mental ill health to start physical activity in the community [ 19 , 49 , 52 ], and that this support should be provided by someone who is trusted and/or well-known to the individual [ 19 , 53 ], such as health professionals [ 54 ], family members or friends [ 55 ]. The interpersonal relationship between the participant and their support team has been shown to play a big role in giving individuals with serious mental illness the confidence to start a new physical activity [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The professionals have an important role in carrying out the interventions, in motivating and maintaining the clients’ involvement in the interventions (Eklund & Leufstadius ; Lassenius et al . ), and in implementation of new ways of working (Eklund & Leufstadius ; Grol & Grimshaw ). Consequently, the professionals’ views are central and the aim of this study was thus to investigate their expectations and experiences of the project Culture and Health.…”
Section: Introductionmentioning
confidence: 99%